A Fatal Contamination: Roger Caillois on Gambling—a “Theme” of (Late) Modern Culture - Cosgrave, Jim (Critical Gambling Studies, 2024)
This article returns to Roger Caillois’ analysis of gambling in his classic text Man, Play, and Games, to provide a framework for understanding the place of widespread legal gambling in late modern culture. The discussion begins with Caillois’ response to Johan Huizinga’s formulations of play and exclusion of gambling from the world of play and games. It then proceeds with Caillois’ rehabilitation of games of chance as culturally significant phenomena. Drawing on some of the central themes of Man, Play, and Games, contemporary gambling is then analyzed, and factors such as the cultural and economic shaping of the social distribution of agon (competition) and alea (chance) provide the basis for an interpretation of the contemporary pervasiveness of games of chance as a socially- and culturally- situated historical phenomenon and “theme” of late modern culture. In this culture, the spatial and temporal boundaries that both Huizinga and Caillois claim mark play off from everyday life have been blurred in the case of gambling games. The article also posits that alea not only “complements” agon, but competes with it, as alea has been legitimated as a social and economic ethic.